Improved performance of GaAs tunnel diode by embedding InAs quantum dot layer for tandem solar cells. (29th May 2015) - Park, Kwang Wook; Kang, Seok Jin; Ravindran, Sooraj; Min, Jung Wook; Lee, Soo Kyung; Park, Min Su; Lee, Yong Tak
Abstract: GaAs tunnel diodes (TDs) embedded with an InAs quantum dot (QD) layer were grown and their performance was compared with that of TDs without a QD layer. The TDs embedded with a QD layer showed enhanced peak tunnel current density and lower differential resistivity at zero bias compared with the TDs without a QD layer. The samples were then annealed to mimic the overlayer growth process. It was found that the performance degradation after annealing was smaller for the QD-layer-embedded TDs. The improved characteristics of the QD-layer-embedded GaAs TDs make them advantageous for interconnecting unit cells in tandem solar cells.